IMMUNE RESPONSE UPON THE ADMINISTRATION OF RECOMBINANT PROTEIN ANTIBODIES Ag-38 KDa Mycobacterium tuberculosis AND RIFAMPICIN EX-VIVO. - Mardining Raras, Tri Yudhani; Fahrinda, Almira; Yuliati, Yuliati; Nurhidayati, Dwi Yuni; Sujuti, Hidayat; Prawiro, Sumarno Reto (African Journal of Infectious Diseases (AJID), 2022)
Background: Making a granuloma model resembling latent tuberculosis in vitro is needed quickly and efficiently to be used as an effective therapy. This study aimed to form efficient granulomas, increase cellular immunity and humoral immunity, and evaluate growth on media using recombinant protein antibody Ag38kDa, Rifampicin, and a combination of both. Peripheral Blood Mononuclear Cell (PBMC) in vitro is derived from a healthy individual separated from monocytes and lymphocytes. Materials and Methods Monocytes are matured into macrophages and then combined macrophages and lymphocytes to the Roswell Park Memorial Institute (RPMI) medium. Flow cytometry analysis was used to count the number of cells, and cytokine levels were measured using ELISA. The result from the treatment was planted on the Lowenstein-Jensen medium. Results: The results from the study showed that granulomas could form after one-day post-treatment with Mycobacterium tuberculosis (M.tb). A significant increase in immune response occurred in the number of macrophages, Th1, and Tregs in the combination group compared to the Mtb infection group. The number of Th2 and Th17 cells in the combination group was compared with the control but not significantly. TNF-α cytokine levels increased in the combination group compared to Mtb infection, while in IL-4, we found between all groups, there was no significant difference. Bacterial colonies on culture in the Lowenstein-Jensen medium were only seen in positive controls. Conclusion: Our study concluded that administration of a combination of Ag38kDa and rifampicin recombinant protein antibodies could inhibit granuloma formation and enhance immune response and inhibit bacterial growth on